Dairy Effluent-Saturated Biochar’s Short-Term Effects on Vigna unguiculata and Cynodon dactylon Performance and Soil Properties - Lisandro J. Entio; Cosette B. Taggart; James P. Muir; Eunsung Kan; Jeff A. Brady; Olabiyi Obayomi (Plants, 2024)
We compared the effects of wood-, manure-, and blend-derived biochar (BC) saturated/unsaturated with dairy effluents on Vigna unguiculata and Cynodon dactylon performance and soil characteristics in a greenhouse pot study. Plant samples were assayed for herbage and root dry weight and N and C percentages. Soil samples were assayed for nutrients, pH, and conductivity. Variance analysis, Tukey’s tests, Pearson’s correlations, and multiple regression analysis were performed. The performance of C. dactylon was not affected. V. unguiculata’s herbage and root production responded negatively to manure BC and 2% of any BC, respectively, which is mainly explained by the conductivity and soil P increase, respectively. When V. unguiculata was grown, BC inclusion decreased NO3-N and increased the soil P content. When C. dactylon was grown, only P was altered (increased) when manure or the blend BC were applied. The soil total C increased as the BC loading rate increased. The application of high BC rates was detrimental for V. unguiculata, but showed a neutral effect for C. dactylon. To improve dairy waste recycling, saturated 1% blend BC and saturated 2% blend or manure BC could be applied to V. unguiculata and C. dactylon, respectively, with no short-term negative impacts. Only wood BC avoided soil P build-up. BC application increased the soil total C, showing potential for C sequestration.